Computational Thinking and Modeling: A Quasi-Experimental Study of Learning Transfer - Line Have Musaeus; Peter Musaeus (MDPI AG, 2024)
This quasi-experimental study investigated the impact of computational learning activities on high school students' computational thinking (CT) and computational modeling (CM) skills. High school students (n = 90) aged 16 to 19 engaged in activities using computer models versus textbook-based models in mathematics and social science. The results indicated that students using computer models showed significant improvements in CT and CM skills compared to their peers in conventional learning settings. However, a potential ceiling effect in the CT assessments suggests that the test may not fully capture the extent of skill development. These findings highlight the importance of integrating computational learning activities in education, as they enhance students' abilities to apply these skills beyond the classroom.